Synthesis of a sucrose-based macrocycle with unsymmetrical monosaccharides "arms" - Tiara, Karolina; Potopnyk, Mykhaylo A.; Jarosz, Sławomir (Beilstein Journal of Organic Chemistry, 2018)
An efficient methodology for the selective substitution of both terminal positions (C6 and C6’) in 1’,2,3,3’,4,4’-hexa-O-benzylsucrose with different unsaturated monosaccharide units is presented. Such a highly functionalized intermediate was cyclized under RCM conditions to afford a macrocyclic derivative containing a 31-membered ring in 26% yield.
Keywords: chiral macrocycles; ring-closing metathesis; sucrose

(untitled) - Zhang, X.; Yin, J.; Yoon, J. (Chem. Rev., 2014)

(untitled) - Kolesnichenko, I. V.; Anslyn, E. V. (Chem. Soc. Rev., 2017)

(untitled) - Amato, M. E.; Ballistreri, F. P.; Gentile, S.; Pappalardo, A.; Tomaselli, G. A.; Toscano, R. M. (J. Org. Chem., 2010)

(untitled) - Akdeniz, A.; Minami, T.; Watanabe, S.; Yokoyama, M.; Ema, T.; Anzenbacher, P., Jr (Chem. Sci., 2016)

(untitled) - McConnell, A. J.; Beer, P. D. (Angew. Chem., Int. Ed., 2012)

(untitled) - Ema, T.; Ura, N.; Eguchi, K.; Ise, Y.; Sakai, T. (Chem. Commun., 2011)

(untitled) - Caricato, M.; Leza, N. J.; Gargiulli, C.; Gattuso, G.; Dondi, D.; Pasini, D. (Beilstein J. Org. Chem., 2012)

(untitled) - Pu, L. (Acc. Chem. Res., 2012)

(untitled) - Ema, T.; Yokoyama, M.; Watanabe, S.; Sasaki, S.; Ota, H.; Takaishi, K. (Org. Lett., 2017)

(untitled) - Brea, R. J.; Reiriz, C.; Granja, J. R. (Chem. Soc. Rev., 2010)

(untitled) - Quinn, T. P.; Atwood, P. D.; Tanski, J. M.; Moore, T. F.; Folmer-Andersen, J. F. (J. Org. Chem., 2011)

(untitled) - Šolomek, T.; Powers-Riggs, N. E.; Wu, Y.-L.; Young, R. M.; Krzyaniak, M. D.; Horwitz, N. E.; Wasielewski, M. R. (J. Am. Chem. Soc., 2017)

(untitled) - Potopnyk, M. A.; Jarosz, S. (Adv. Carbohydr. Chem. Biochem., 2014)

(untitled) - Jarosz, S.; Potopnyk, M. A.; Kowalski, M. (Carbohydr. Chem., 2014)

Click Chemistry in Glycoscience - Potopnyk, M. A.; Jarosz, S. (“Sweet” Sucrose Macrocycles via a “Click Chemistry” Route, 2013)

(untitled) - Jarosz, S.; Listkowski, A.; Lewandowski, B.; Ciunik, Z.; Brzuszkiewicz, A. (Tetrahedron, 2005)

(untitled) - Potopnyk, M. A.; Lewandowski, B.; Jarosz, S. (Tetrahedron: Asymmetry, 2012)

(untitled) - Potopnyk, M. A.; Jarosz, S. (Eur. J. Org. Chem., 2013)

(untitled) - Potopnyk, M. A.; Cmoch, P.; Jarosz, S. (Org. Lett., 2012)

(untitled) - Potopnyk, M. A.; Jarosz, S. (Monatsh. Chem., 2013)

(untitled) - Łęczycka-Wilk, K.; Dąbrowa, K.; Cmoch, P.; Jarosz, S. (Org. Lett., 2017)

(untitled) - Barros, M. T.; Petrova, K. T.; Singh, R. P. (Eur. Polym. J., 2010)

(untitled) - Petrova, K. T.; Potewar, T. M.; Ascenso, O. S.; Barros, M. T. (Carbohydr. Polym., 2014)

(untitled) - Petrova, K. T.; Correia-da-Silva, P.; Crucho, C. I. C.; Barros, M. T. (Curr. Org. Chem., 2014)

(untitled) - Crucho, C. I. C.; Barros, M. T. (J. Mater. Chem. B, 2014)

(untitled) - Raposo, C. D.; Petrova, K. T.; Barros, M. T.; Calhelha, R. C.; Soković, M.; Ferreira, I. C. F. R. (Med. Chem., 2016)

(untitled) - Petrova, K. T.; Barros, M. T.; Calhelha, R. C.; Soković, C.; Ferreira, I. C. F. R. (Med. Chem. Res., 2018)

(untitled) - Łęczycka, K.; Jarosz, S. (Tetrahedron, 2015)

(untitled) - Wakchaure, S.; Einsiedel, J.; Waibel, R.; Gmeiner, P. (Synthesis, 2012)

(untitled) - Mao, Z.-Y.; Si, C.-M.; Liu, Y.-W.; Dong, H.-Q.; Wei, B.-G.; Lin, G.-Q. (J. Org. Chem., 2017)

(untitled) - Bernet, B.; Vasella, A. (Helv. Chim. Acta, 1979)

(untitled) - Bernet, B.; Vasella, A. (Helv. Chim. Acta, 1979)

(untitled) - Jensen, T.; Mikkelsen, M.; Lauritsen, A.; Andresen, T. L.; Gotfredsen, C. H.; Madsen, R. (J. Org. Chem., 2009)

(untitled) - Fürstner, A.; Weidmann, H. (J. Org. Chem., 1989)

(untitled) - Fürstner, A.; Weidmann, H. (J. Org. Chem., 1990)

(untitled) - Gaweł, A.; Jarosz, S. (J. Carbohydr. Chem., 2010)

(untitled) - Szyszka, Ł.; Osuch-Kwiatkowska, A.; Potopnyk, M. A.; Jarosz, S. (Beilstein J. Org. Chem., 2017)

(untitled) - Mancuso, A. J.; Huang, S.-L.; Swern, D. (J. Org. Chem., 1978)